Depletion of gram-positive bacteria impacts hepatic biological functions during the light phase - Oh, Penny Hui Yun (2019)
Living organisms display internal biological rhythms, which are an evolutionarily conserved adaptation to the environment that drives their rhythmic behavioral and physiological activities. The gut microbiota has been proposed, in association with diet, to regulate the intestinal peripheral clock. However, the effect of gut dysbiosis on liver remains elusive, despite that germfree mice show alterations in liver metabolic functions and the hepatic daily rhythm. We analyzed whether the disruption of gut microbial populations with various antibiotics would differentially impact liver functions in mice. Our results support the notion of an impact on the hepatic biological rhythm by gram-positive bacteria. In addition, we provide evidence for differential roles of gut microbiota spectra in xenobiotic metabolism that could protect against the harmful pharmacological effects of drugs. Our results underscore a possible link between liver cell proliferation and gram-positive bacteria.